2018
DOI: 10.4103/aer.aer_90_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of oral melatonin with oral alprazolam used as a premedicant in adult patients undergoing various surgical procedures under general anesthesia: A prospective randomized placebo-controlled study

Abstract: Background and Aims:Preoperative anxiety is a major concern in patients undergoing any surgical procedure. Various drugs have been used to alleviate it. This study aims to compare the effects of oral melatonin versus oral alprazolam on preoperative anxiety, sedation, orientation, and cognitive function.Materials and Methods:A total of 90 adult patients were randomly allocated into three groups. Group M (n = 30) received oral melatonin 3 mg (2 tablets); Group A (n = 30) received oral alprazolam 0.25 mg (2 table… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…The results of studies by Khare et al [14] and Lotfy and Ayaad [15] align with that of the current study. Khare et al discovered that premedication with oral melatonin (6 mg) serves as an effective alternative to alprazolam, offering improved anxiolysis, less sedation, and maintenance of cognitive and psychomotor function [14]. Furthermore, a systemic literature review by Campbell et al revealed that perioperative melatonin, administered in daily doses of 2-8 mg for one to nine days, starting on the evening before or the day of surgery, reduced the incidence of postoperative complications such as anxiety and delirium following major surgeries [16].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of studies by Khare et al [14] and Lotfy and Ayaad [15] align with that of the current study. Khare et al discovered that premedication with oral melatonin (6 mg) serves as an effective alternative to alprazolam, offering improved anxiolysis, less sedation, and maintenance of cognitive and psychomotor function [14]. Furthermore, a systemic literature review by Campbell et al revealed that perioperative melatonin, administered in daily doses of 2-8 mg for one to nine days, starting on the evening before or the day of surgery, reduced the incidence of postoperative complications such as anxiety and delirium following major surgeries [16].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings regarding the analgesic effect of melatonin align with earlier studies, further supporting the efficacy of melatonin as a premedication agent [ 3 , 9 , 11 - 13 ]. The results of studies by Khare et al [ 14 ] and Lotfy and Ayaad [ 15 ] align with that of the current study. Khare et al discovered that premedication with oral melatonin (6 mg) serves as an effective alternative to alprazolam, offering improved anxiolysis, less sedation, and maintenance of cognitive and psychomotor function [ 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…Numerous studies have demonstrated the efficacy of melatonin in reducing perioperative anxiety. A prospective clinical study ( Khare et al, 2018 ) found that administering 6 mg of melatonin orally to adult patients 120 min before the induction of general anesthesia provides superior anti-anxiety effects compared to administering 0.25 mg of alprazolam to adult patients. Melatonin administration resulted in less sedation and better preservation of cognitive and psychomotor function.…”
Section: Melatonin For Anti-anxiety and Improvement Of Sleep Disorder...mentioning
confidence: 99%
“…В этом отношении М рассматривается как альтернатива (или дополнение) кортикостероидам или опиоидам, которые, в отличие от М, оказывают иммуносупрессивное действие. Кроме того, М может быть альтернативой бензодиазепиновому анксиолитику алпразоламу при хирургических процедурах [36]. М также может быть востребован в качестве вспомогательной терапии, улучшающей качество жизни больных, так как бессонница, тревожность, беспокойство, депрессия, боль и другие симптомы сопутствуют онкологическим заболеваниям [37][38][39].…”
Section: обзоры литературыunclassified